Valence scaling of dynamic facial expressions is altered in high-functioning subjects with autism spectrum disorders: an fMRI study - Rahko, Jukka; Bölte, Sven (Journal of autism and developmental disorders, 2011)
FMRI was performed with the dynamic facial expressions fear and happiness. This was done to detect differences in valence processing between 25 subjects with autism spectrum disorders (ASDs) and 27 typically developing controls. Valence scaling was abnormal in ASDs. Positive valence induces lower deactivation and abnormally strong activity in ASD in multiple regions. Negative valence increased deactivation in visual areas in subjects with ASDs. The most marked differences between valences focus on fronto-insular and temporal regions. This supports the idea that subjects with ASDs may have difficulty in passive processing of the salience and mirroring of expressions. When the valence scaling of brain activity fails, in contrast to controls, these areas activate and/or deactivate inappropriately during facial stimuli presented dynamically.
Gesehen am 17.05.2018